A Comparison of John Dewey and E. D. Hirsch's Thoughts on Determining Quality Educational Goals - Darmawati.R; Prayitno, Mustofa Aji; Solehuddin, Moh.; Sappaile, Baso Intang; Cahyono, Didik (COMPETITIVE: Journal of Education, 2023)
This paper explores the views of John Dewey and E. D. Hirsch on determining quality educational goals, and compares the similarities and differences between their approaches. The main objective of this research is to provide a comprehensive understanding of the two prominent educational theorists and their ideas on quality educational goals, and to examine how their approaches differ and overlap. To achieve this objective, the research methodology adopted in this study is a comparative analysis of the two thinkers' views on education. The study begins with a thorough review of the literature on the educational theories of Dewey and Hirsch, followed by a comparative analysis of their approaches. The comparative analysis includes an examination of their perspectives on curriculum development, experiential learning, cultural literacy, and knowledge-based education. The data collected from the literature review and comparative analysis is then synthesized to develop a comprehensive understanding of the similarities and differences between Dewey and Hirsch's approaches to determining quality educational goals. The findings of this research suggest that while Dewey and Hirsch's approaches differ in their emphasis on experiential learning versus cultural literacy, they share a common goal of providing a quality education that prepares students for active and engaged citizenship. Additionally, both Dewey and Hirsch emphasize the importance of effective curriculum development and individualized learning. Education policymakers and practitioners can draw on the insights provided by this research to develop a holistic approach to education that incorporates the strengths of both Dewey and Hirsch's perspectives.